KAJIAN TENTANG PELAKSANAAN PENCATATAN SIPIL DITINJAU DARI PERSPEKTIF UU NO. 23 TAHUN 2006 TENTANG ADMINISTRASI KEPENDUDUKAN DI KABUPATEN BANTUL - Suwarni, Sri (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2010)
The research aims to figure out the implementation of vital statisticsÂ in Bantul Regency that in line with Law No.23/2006, to find out problems in the implementation of this vital statistics, and to define efforts done by the officials in dealing with problem in the implementation of vital statistics with the presence of aforementioned regulation. This research was conducted in both library and field research methods. The data attained from both library and field research, analyzed in qualitative approach. Law No. 23/2006 has recently been implemented in Local Regulation of Bantul Regency No. 26/2008 on the implementation of demographic administration and Bantul Regent Regulation No. 16/2008 on Birth Certificate Record. Problems occurred on vital statistics during transition period of Law application are quality of human resources which is frankly speaking still insufficient to deal with high demand from the residents on service of official documents, especially birth certificate, and deficiency of facilities to support the implementation of vital statistics. The officials has conducted Demography and Vital Statistics Service in order to meet the high demand on providing official documents, are maximizing its service and using available facilities in Demography and Vital Statistics Service, also in Licensing Service.Keywords: demographic administration, vital Statistics, Licensing Service.